2016
DOI: 10.1111/etho.12110
|View full text |Cite
|
Sign up to set email alerts
|

Clinging to Hope through Education: The Consequences of Hope for Rural Laborers in Telangana, India

Abstract: Education is for marginalized people in agrarian Telangana, India, the means to getting ahead, at the same time that structural conditions have diminished its potential. This article considers the consequences of education's failures for parents’ positioning within a society that is purported to be “moving forward.” I draw upon Berlant (2011) and Ahmed (2010) as a starting point to explore the possibility that the idea of progress through education is critical to one's sense of self, anchoring the self to conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…This caused them stress as they mourned a lost year of their children's education. Scholars have found that rural parents in India often sustain their own hope for the future through investing in children's education (Jakimow 2016). Perhaps a more enduring yet subtle impact will be on women's diminishing emotional resources to sustain hope through their children's education: One year of my son's life is lost and as per age he will be behind because in the future if he sits for tests for army, etc., then it will be problematic.…”
Section: Resultsmentioning
confidence: 99%
“…This caused them stress as they mourned a lost year of their children's education. Scholars have found that rural parents in India often sustain their own hope for the future through investing in children's education (Jakimow 2016). Perhaps a more enduring yet subtle impact will be on women's diminishing emotional resources to sustain hope through their children's education: One year of my son's life is lost and as per age he will be behind because in the future if he sits for tests for army, etc., then it will be problematic.…”
Section: Resultsmentioning
confidence: 99%
“…Tanya Jakimow ( 2016 , p. 11) defines development contexts as ‘locales thick with the discourses, practices, and institutions of international development’. Describing the development context of Indonesia, Li ( 2007 , p. 1) notes that ‘talk of improvement is everywhere’, as are programmes that seek to improve the condition of a specific or general population (Li 2007 , p. 1).…”
Section: Methodological Challenges and Solutionsmentioning
confidence: 99%
“…Development discourse is thick with aspirations (Frye 2012 ; Jakimow 2016 ). Planning for and bringing about desired forms of change is key to development practice and the longing for a better life constitutes a main driving force for people’s continued engagement with development interventions despite its all-too-frequent disappointments (De Vries 2007 ; High 2014 ; Li 2007 ).…”
Section: Defining Aspirationsmentioning
confidence: 99%
“…Everyday discourses and practices in camp schools are oriented toward renewing young people's optimism and trust in the promise of a better future, more so than pedagogical or curricular goals that might enable them to construct those futures. Related research theorizes that hope projected through education functions as a survival mechanism for young people enduring contexts of uncertainty, risk, and marginalization (Jakimow, ; Mains, ). Hope is “an aspect of future making… intertwined with social relationships and institutions” (Cole & Durham, , p. 16), but many worry that schools too easily manufacture false hope (Duncan‐Andrade, ; Fine & Burns, ).…”
Section: Methodsmentioning
confidence: 99%